2022
DOI: 10.21037/atm-22-2730
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review on the association of high intraocular pressure and glaucoma in patients with retinal vein occlusion

Abstract: Background and Objective: Retinal vein occlusion (RVO) is a major cause of vision loss and elevated intraocular pressure (IOP), high ocular perfusion pressure, and glaucoma are known ophthalmic risk factors for RVO. The aim of this paper is to provide the update on the association and management of high IOP/ glaucoma and RVO.Methods: A literature review was performed in PubMed and Medline until May 2022 utilizing specific keywords and cross-matched reference lists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…Many studies have examined the relationship between glaucoma, specifically POAG, and risk for RVO [4]. Yin et al demonstrated in their meta-analysis that POAG is significantly associated with RVO risk (OR: 5.03; 95% CI: 3.97 to 6.37) [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have examined the relationship between glaucoma, specifically POAG, and risk for RVO [4]. Yin et al demonstrated in their meta-analysis that POAG is significantly associated with RVO risk (OR: 5.03; 95% CI: 3.97 to 6.37) [3].…”
Section: Discussionmentioning
confidence: 99%
“…Glaucoma, an ocular disorder characterized by optic nerve damage and visual field loss, has been implicated in the pathogenesis of RVO [3]. Specifically, the association between RVO and primary open angle glaucoma (POAG) has been investigated in numerous studies, showing a significantly higher prevalence of RVO in patients with POAG compared to the general population [3,4]. Different pathogenic mechanisms have been proposed, implicating intraocular pressure which is a well-established and modifiable risk factor for glaucoma.…”
Section: Introductionmentioning
confidence: 99%
“…6 High intraocular pressure is sometimes responsible for CRVO and has been documented in several case reports since the twentieth century but the reported case in this article had normal ocular pressure. 12,13,14 CRVO can be of two types. The mild type occurs due to leaky retinal vessels, manifesting with blurred vision on waking up in the morning and improving during the daytime.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has some common pathogenetic theories with the occurrence of retinal vein occlusions, they seem to be valid only for a small category of patients [ 4 ]. Several studies already demonstrated that glaucoma represents a higher risk for developing retinal vein occlusions [ 5 , 6 ], and the reasons seem to be the modifications produced at the lamina cribrosa, which consequently have an impact on the path of the vein passing through the optic nerve head [ 4 ]. Nevertheless, opinions and results vary when discussing the morphological and functional impact of glaucoma association with retinal vein occlusions.…”
Section: Introductionmentioning
confidence: 99%